Implementation of local government information system: evidence from BPKAD in West Sumbawa Regency - Eka Puspitasari; Rr. Sri Pancawati Martiningsih; Nurabiah (International Journal of Applied Finance and Business Studies, 2023)
This study aims to determine how the implementation of the Local Government Information System (SIPD) in the framework of the expenditure administration process at the Regional Asset and Financial Management Agency (BPKAD) in West Sumbawa Regency. This study used a descriptive research method with a qualitative approach. Data were collected through observation, interviews, and documentation. The informants in this study were the Head of the Treasury Section, the Head of the Shopping Administration Subdivision, and the Financial Verifier of the Expenditure Administration Subdivision. Local Government Information System (SIPD) in the process of administering expenditures using the Edward III model in the form of communication, resources, dispositions, and bureaucratic structures has not run optimally. Communication and coordination between authorities still have obstacles. As a result, it can hinder the process of administering spending, but the information provided by policymakers has been consistent and clear. Judging from the resource factors, both human resources, authority, and information are sufficient, but there are still constraints on facility resources because SIPD is not perfect and is still in the development stage. The unavailability of incentives for SIPD implementers is expected to spur enthusiasm for the implementation of SIPD, there is a Standard Operational Procedure (SOP) for the use of SIPD. The results of this study are expected to have implications regarding policy implementation based on George C. Edward's theory that the information system used can affect the level of performance and productivity of employees and organizations. And it is hoped that the results of this research can be used as evaluation material for local governments.